Welfare effects of VAT reforms: A general equilibrium analysis - Brita Bye; Birger Strøm; Turid Åvitsland (Statistics Norway, Research Department, 2003)
Indirect taxes such as value added taxes (VAT) generate a substantial part of tax revenue in many countries. This paper analyses welfare effects of different reforms in the Norwegian system of indirect taxation. The main reform studied is the introduction of a uniform VAT rate on all goods and services. The Norwegian political VAT reform of 2001 is also analysed. The reforms are analysed by using an intertemporal CGE model for the Norwegian economy. A non-uniform VAT system gives a welfare loss compared to a uniform VAT system.
Keywords: D58; H20; 330; Indirect taxation; VAT reforms; Dynamic general equilibrium analysis